The impact of the visual, auditory, and kinesthetic model on motivation and learning outcomes of Islamic Elementary School students - Lidya Hastuti Dahliana; Aceng Jaelani; Ummi Nur Rokhmah (Journal of Integrated Elementary Education, 2023)
Motivation is crucial in guiding student behavior and engagement during the learning process. Therefore, it is essential to improve motivation by implementing a customized learning model that addresses individual needs and learning styles. This study aims to investigate the influence of the visual, auditory, and kinesthetic (VAK) learning model on students' motivation and academic achievement at Salafiyah Madrasah Ibtidaiyah, Cirebon City. A one-group pretest-posttest research design was used. Data were collected through questionnaires and tests. The data were analyzed using descriptive statistics, N-gains, t-tests, and simple linear regression. The results indicate that 59.76% of the students agreed or strongly agreed with the implementation of the VAK model, while 17.51% disagreed or strongly disagreed, and 22.70% were undecided. The implementation of the VAK model significantly improved learners' motivation and engagement in the educational process, as evidenced by a mean score of 79% on the questionnaire. Post-test results showed a significant increase in student learning outcomes, with an average score of 79.1 in the post-test compared to 60.7 in the pre-test. The coefficient of determination test results demonstrated a 47.5% increase, while the average N-gain value revealed a medium-level improvement of 0.4351. These findings provide useful insights for educators and researchers seeking to increase student motivation and achievement by designing VAK models that provide effective and engaging learning experiences.